2022
DOI: 10.1093/cid/ciac759
|View full text |Cite
|
Sign up to set email alerts
|

Same-Day Antiretroviral Therapy Initiation as a Predictor of Loss to Follow-up and Viral Suppression Among People With Human Immunodeficiency Virus in Sub-Saharan Africa

Abstract: Background Treat-All guidelines recommend initiation of antiretroviral therapy (ART) for all people living with HIV (PLHIV) on the day of diagnosis when possible, yet uncertainty exists about the impact of same-day ART initiation on subsequent care engagement. We examined the association of same-day ART initiation with loss to follow-up and viral suppression among patients in 11 sub-Saharan African countries. Methods We inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Therefore, we were not able to assess adherence or other clinical or sociodemographic factors contributing to an unsuppressed VL. Third, similar to other cohorts in sub-Sahara Africa [ 20 , 21 ], there was a considerable amount of loss to follow-up that was similar for both the NNRTI and dolutegravir group. Fourth, per national guidelines, VL tests are routinely done once per year only, making the differentiation between viral blips and LLV impossible.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, we were not able to assess adherence or other clinical or sociodemographic factors contributing to an unsuppressed VL. Third, similar to other cohorts in sub-Sahara Africa [ 20 , 21 ], there was a considerable amount of loss to follow-up that was similar for both the NNRTI and dolutegravir group. Fourth, per national guidelines, VL tests are routinely done once per year only, making the differentiation between viral blips and LLV impossible.…”
Section: Discussionsupporting
confidence: 75%
“…We found several other publications that reported the rate of same-day initiation in various countries in sub-Saharan Africa, mostly at earlier time periods than our study, which was conducted between 2018 and 2020. A multi-country cohort study using data from the IeDEA Network through 2018, including South Africa but not Malawi or Zambia, reported an overall rate of SDI of 64%[9]. Three studies from South Africa were all completed roughly one year earlier than our study, in 2017-2018.…”
Section: Discussionmentioning
confidence: 84%
“…Other analyses have shown that patients entering HIV care in the era of universal treatment initiate treatment more rapidly [ 4 , 5 ] and that the expansion of HIV treatment eligibility criteria has resulted in the treatment of patients with earlier stage HIV disease [ 38 ]. While earlier treatment initiation is associated with improved clinical outcomes and reduced onward HIV transmission, rapid initiation of treatment after enrollment in HIV care is also associated with lower retention in care [ 39 , 40 ], and qualitative research has suggested that distress and uncertainty about HIV diagnosis, concerns about stigma, fear of lifelong medication, and other patient-level factors may contribute to attrition and lower treatment adherence among those rapidly initiating treatment, particularly among patients with early stage disease who do not feel unwell [ 41 , 42 ]. Our observed decreases in retention after ART initiation in the era of universal treatment may reflect the fact that some patients, who would have been LTC prior to ART initiation before guideline adoption, initiated ART more rapidly.…”
Section: Discussionmentioning
confidence: 99%